Ferrocenes as Building Blocks in Molecular Rectifiers and Diodes - Mark E. Welker (Molecules, 2018)
Ferrocenes have recently been reported as components of a number of molecular circuits. This short review covers reports of ferrocenes in molecular rectifiers and diodes which have appeared in the last 10 years.